Sosialisasi Pembimbingan Teknik Penulisan Skripsi pada Dosen di Lingkungan Pusat Kajian Ilmu Ekonomi (Puskanomi) Universitas Indraprasta PGRI, Jakarta (PUNDIMAS: Publikasi Kegiatan Abdimas, 2023)
This activity aims to provide an understanding regarding the guidance of thesis writing techniques to lecturers at the Center for Economic Studies (Puskanomi) Indraprasta University PGRI, Jakarta. The method used in this activity is the socialization method using Zoom Meeting media. The activity was carried out online with a duration of two hours. The partners in this activity were lecturers at the Center for Economic Studies (Puskanomi) Indraprasta PGRI University, Jakarta who were assigned as thesis technical advisors. The results of this activity show that there is still no common perception regarding the interpretation of what is conveyed in the Thesis Writing Guidelines used. With this activity, several polemics that often occur can eventually be mediated and agreed to be implemented in the mentoring process. This activity proves the importance of equalizing perceptions in achieving uniformity in thesis writing. This activity is expected to become a routine agenda that is carried out before the thesis guidance assignment begins and is assigned to the supervisors.